2015
DOI: 10.1007/s00432-015-2036-9
|View full text |Cite
|
Sign up to set email alerts
|

Amplified HMGA2 promotes cell growth by regulating Akt pathway in AML

Abstract: HMGA2 is predominantly amplified and expressed in AML cells, and that aberrant expression of HMGA2 induces AML cell proliferation through the PI3K/Akt/mTOR signaling pathway. Inhibition of HMGA2 expression represents an attractive target for AML therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 27 publications
7
53
0
1
Order By: Relevance
“…The association between HMGA2 and cancer proliferation has been reported previously . In general, HMGA2 knockdown could inhibit cell growth in several types of cancer, which was similar to our findings in LAC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The association between HMGA2 and cancer proliferation has been reported previously . In general, HMGA2 knockdown could inhibit cell growth in several types of cancer, which was similar to our findings in LAC.…”
Section: Discussionsupporting
confidence: 92%
“…Apart from working as a transcription co‐regulator, HMGA2 could also directly regulate gene transcription activation . HMGA2 could function as a regulator of cell proliferation and its expression is increased in many types of human tumor tissues . HMGA2 is also suggested to be involved in EMT regulation in many epithelial carcinomas .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that there was a negative correlation between miR-211 and HMGA2 expression in GBM tissues. HMGA2 is able to activate the AKT signaling pathway [27]. AKT could lead to phosphorylation of β-catenin and promotes Wnt pathway signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In these cancers, the overexpression of HMGA2 is reported to enhance tumour progression involving the PI3K/Akt/mTOR, HMGA2-TET1-HOX signalling pathways [13,14] and tumour invasiveness by inducing transforming growth factor-β receptor II (TGFβRII) and SMAD transducers in the TGFβ signalling pathway [15,16]. …”
Section: Introductionmentioning
confidence: 99%